Lobbying for Industrialization: Theory and Evidence - Dmitry Veselov; Alexander Yarkin (Institute of Labor Economics (IZA), 2024)
Industrial policies, such as infrastructure investments and export tariffs, affect the allocation of labor and incomes across sectors, attracting substantial lobbying efforts by special interest groups. Yet, the link between structural change and lobbying remains underexplored. Using more than 150 years of data on parliamentary petitions in USA and Britain, we measure historical lobbying and document several stylized facts. First, lobbying over industrial policies follows a hump-shaped path in the course of structural change, while agricultural lobbying steadily declines. Second, big capitalists (manufacturers, merchants) are most active in lobbying for industrialization. Third, industrial concentration increases progressive lobbying, while concentrated landownership slows it down. We explain these patterns in a simple model of structural change augmented with a heterogeneous agents lobbying game. Model simulations match the dynamics of structural change, inequality, and lobbying for industrialization in the British data.
Keywords: D33; D72; N10; N41; O14; O41; O43; P00; 330; political economy; structural change; lobbying; wealth distribution; growth